The Aedes aegypti (Diptera: Culicidae) hsp83 Gene Promoter Drives Strong Ubiquitous DsRed and ZsGreen Marker Expression in Transgenic Mosquitoes. Issue 6 (24th July 2021) - Webster, Sophia H; Scott, Maxwell J
Abstract: Transgenic strains of the mosquito disease vector Aedes aegypti (L.) are being developed for population suppression or modification. Transgenic mosquitoes are identified using fluorescent protein genes. Here we describe DsRed and ZsGreen marker genes driven by the constitutive Ae. aegypti heat shock protein 83 ( hsp83 ) promoter in transgenic mosquitoes. Transgenic larvae and pupae show strong full body expression of the red and green fluorescent proteins. This greatly assists in screening for transgenic individuals while making new or maintaining already established lines. Transient marker gene expression after embryo microinjection was readily visible in developing larvae allowing the separation of individuals that are more likely to produce transgenic offspring. The strongly expressed marker genes developed in this study should facilitate the detection of transgenic Ae. aegypti larvae or pupae in the field.